Predictors of quality of life among adults with self-reported cancer related cognitive impairment. Issue 6 (13th March 2023) - Maeir, Talia; Nahum, Mor; Makranz, Chen; Tsabari, Shani; Peretz, Tamar; Gilboa, Yafit
Abstract: Objective: The purpose of the current study was to examine the unique contribution of personal and medical factors, objective and subjective cognition, and self-efficacy to the explained variance of quality of life (QoL) among survivors with self-reported cancer related cognitive impairment (CRCI). Method: Seventy-three cancer survivors (non-central nervous system) with CRCI (mean age: 50.85 ± 10.82 years old, mean years post-treatment: 3 ± 2.7) participated in this cross-sectional study. QoL was assessed using the Functional Assessment of Cancer Therapy (FACT)–GP, while the cognitive function was assessed both objectively using tests of attentional control, speed of processing and sustained attention, and subjectively using the FACT-Cognition perceived cognitive impairments (FACTcog-PCI) subscale. Self-efficacy was assessed using the New General Self-Efficacy Scale (NGSE). Results: A hierarchical multiple linear regression analysis revealed that sustained attention, perceived cognitive impairment and self-efficacy, accounted for 54% of the variance of QoL ( R 2 = 0.543, p < 0.000), each providing a unique contribution to the explained variance (15–20% each) after controlling for age and gender. Conclusions: Considering that these variables may be amenable to change, this model can serve as a conceptual framework for designing effective cognitive treatment options for CRCI. Clinical Trial Registration: ClinicalTrials.gov NCT Implication for rehabilitation: Cancer related cognitive impairment is characterized by difficulties in the speed of processing performance, severe perceived cognitive impairments, and relatively low general self-efficacy. Multi-dimensional assessments including subjective and objective cognition as well as self-efficacy should be administered to cancer survivors with cognitive complaints to understand the underlying mechanisms of their QoL. Integrative cognitive rehabilitation interventions that aim to improve QoL among people with cancer-related cognitive impairment should target sustained attention, perceived cognitive impairment, and self-efficacy.